Anodic and Cathodic Processes In Piperidinium-Based Ionic Liquid Mixtures With AlCl3 - Risbud, Mandar; Kononov, R.; Bucknall, M.; Welch, B.; McCann, J.; Skyllas-Kazacos, M. (Deuton X Ltd, 2012)
Low temperature molten salts based on ionic liquids have received considerable attention over the last 3 decades as potential alternative solvents for aluminium reduction. Recent reports in the literature have identified 1-propyl-1-methylpiperidinium bis(trifluoromethylsulfonyl) amide ([C3mpip][NTf2]) as a promising candidate for low temperature aluminium reduction processes. The formation of aluminium metal deposition was confirmed in these studies by both visual inspection and SEM-EDX analysis in the selected mixtures with AlCl3, but little is known about the anodic processes occurring in the cell. This work presents the results of a preliminary electrochemical study of the anodic and cathodic reactions occurring in the ionic liquid mixtures 1-propyl-1-methylpiperidinium bis(trifluoromethylsulfonyl) amide ([C3mpip][NTf2]) with AlCl3 at different temperatures, concentrations and electrode materials. Analysis of voltammetric responses of [C3mpip][NTf2]-[AlCl3]x for x=0.3 indicated that the anodic process is limited by mass transport for this particular electrolyte composition. In addition, the formation of Cl2 was confirmed to take place at a dimensionally stable anode. Aluminium deposition experiments gave inconsistent results however and gas analysis indicated that the [C3mpip][NTf2]-[AlCl3]x mixture at a prolonged elevated temperature at least partially decomposes into fluoro-carbons and chloro-compounds.